To pool or to pull back? An economic analysis of health data pooling - Bruno Carballa Smichowski; Néstor Duch-Brown; Bertin Martens (European Commission, Joint Research Centre (JRC), 2021)
We present a novel generic theoretical framework to analyze the incentives agents have to engage in n-way data sharing or 'data pooling' and the factors affecting those incentives. Based on the results obtained, we provide policy recommendations aimed at fostering health data pooling. Section 1 develops a baseline framework and multiple variations including zero-sum data pooling games, competing pools and intra-pool negative externalities. The section offers analytical solutions and examples to show under which conditions agents decide to pool data. Section 2 illustrates how different factors can lead to sub-optimal data pooling. Section 3 provides policy recommendations to foster data pooling in the health sector and discusses the conditions under which they can be effective.
Keywords: 330; data pool; health data; data sharing